Physical and Physiological Responses of U-14, U-16, and U-18 Soccer Players on Different Small-Sided Games - Jorge López-Fernández; Javier Sánchez-Sánchez; Jorge García-Unanue; Enrique Hernando; Leonor Gallardo (MDPI AG, 2020)
As most existing studies in youth academies are focused on top players, the objective of this research is to analyze the physical and physiological demands of various small-sided games (SSGs) on different age categories within a sub-elite soccer academy. We evaluated 63 young players from a Spanish sub-elite academy (under 14 = 21; under 16 = 21; under 18 = 21). Players performed four different small-side games focused on possession game (3-a-side; 4-a-side; 5-a-side; 6-a-side). The global indicators of performance and high-intensity actions were recorded through global positioning systems, whereas the heart rate responses were measured using heart rate monitors. Results: Under 16 ran a greater distance at high-intensity velocity than under 14 in the small side games 3v3 and 6v6. Furthermore, under 16 also ran a greater distance at high-intensity velocity than under 18 in the small side game 3v3 (p < 0.01). Under 14 showed greater acceleration at the highest intensity (> 2.75 m/s2) than the other age groups, under 16 and U18 (p < 0.01; ES (effect size) > 1). According to the physiological load, SSG 3v3 presented lower outcomes in Zone 6 (> 95% HRmax) than the small side game 4v4 and the small side game 5v5, in both under 14 and under 16. The workload of SSGs varies depending on the number of players, but also depending on the players' ages. Therefore, when designing the SSGs it is important to consider both the players' ages and the workload that want to be achieved.